2020
DOI: 10.1002/jcla.23373
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of RDW in AKI and mortality in patients with traumatic brain injury

Abstract: Background Red blood cell distribution width (RDW) has been validated valuable in predicting outcome and acute kidney injury (AKI) in several clinical settings. The aim of this study was to explore whether RDW is associated with outcome and AKI in patients with traumatic brain injury (TBI). Methods Patients admitted to our hospital for TBI from January 2015 to August 2018 were included in this study. Multivariate logistic regression analysis was performed to identify risk factors of AKI and outcome in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
(108 reference statements)
3
9
0
Order By: Relevance
“…To diagnose a renal disorder accompanied by a rapid renal function decline, an AKI biomarker that reflects the renal disorder at an early stage is required. AKI biomarkers have been discovered and used in clinical practice, and studies that predict an early diagnosis and prognosis have been reported 10–13 . In this study, we verified the usefulness of U‐NGAL, PCT, and routine laboratory test results as AKI biomarkers in hospitalized adult ICU patients in the emergency department.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…To diagnose a renal disorder accompanied by a rapid renal function decline, an AKI biomarker that reflects the renal disorder at an early stage is required. AKI biomarkers have been discovered and used in clinical practice, and studies that predict an early diagnosis and prognosis have been reported 10–13 . In this study, we verified the usefulness of U‐NGAL, PCT, and routine laboratory test results as AKI biomarkers in hospitalized adult ICU patients in the emergency department.…”
Section: Discussionsupporting
confidence: 59%
“…AKI biomarkers have been discovered and used in clinical practice, and studies that predict an early diagnosis and prognosis have been reported. 10 , 11 , 12 , 13 In this study, we verified the usefulness of U‐NGAL, PCT, and routine laboratory test results as AKI biomarkers in hospitalized adult ICU patients in the emergency department.…”
Section: Discussionsupporting
confidence: 57%
“…Hu et al reported a significant increase in risk of AKI and short and long-term mortality in patients with increased RDW at time of admission in the coronary care unit ( 9 ). Similarly, a trial conducted by Wang et al showed elevated levels of RDW to be an independent predictor for frequency of AKI and mortality in patients with traumatic brain injuries, using a cut-off of 14.25% ( 10 ). Nevertheless, there exists very little information about the relationship between RDW and frequency of AKI and mortality in ARDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the number of investigations and researches on AKI in critically ill patients was continuously increasing and relevant results were discovered. Such as trauma, increased blood lactate, shock, old age, red blood cell distribution width (RDW), and increased procalcitonin were investigated to be independent risk factors for the development of AKI (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%